Therapeutic interaction and verbal behavior in an analytic-behavioral approach (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
The therapeutic interaction in the behavior analysis (BA) is understood as a medium that helps the process of change in behavioral relationships. To understand the aspects that make up this interaction contributes to the identification of success in therapy, increasing accuracy of analysis, its effectiveness, and minimizing failures. This article aimed to present the therapeutic interaction as behavior modification feature from the BA and its relationship to verbal behavior. A definition of therapeutic interaction is presented and discussed as verbal behavior. The main verbal operant that can act altering behavior from the therapeutic interaction are touch, command, intraverbal and autoclitics. Changing the verbal behavior is one of the purposes of therapeutic interaction, because it also changes behavior in a natural environment. Therefore, there is a close relationship between verbal behavior and therapeutic interaction, and analysis of this interaction allows establishing effective changes in client behavior.
Keywords: behavioral analysis; therapeutic interaction; psychotherapy; verbal behavior